Bagana de carnaúba como material alternativo de cama em sistema compost barn para bovinos leiteiros - Sampaio, Lucas Correia de (2019)
Compost bedded pack barns handling requires easy replacement of bedding, as this is a recurring practice in the system, but these materials are often not easily found in all regions of the country, so looking for bedding materials may assist in the costs and management of this system. The objective of this study was to evaluate the thermal attributes of an alternative bed composed of carnauba straw for compost barn and the thermoregulatory, physiological and behavioral responses of confined dairy cows in a semiarid climate. Environmental monitoring operations were performed on a commercial farm located in Russas, Ceará State, Brazil, from May to September 2018. Kriging maps were prepared to visualize the spatial distribution of the bed surface temperature (BST). and internal bed temperature (IBT) in the shed during the morning and afternoon shifts. The environmental parameters were measured by meteorological mini-stations placed in the facility. The wind speed was recorded in both turns. For the environmental analysis, three thermal comfort indexes were calculated: Temperature-Humidity Index (THI), Black Globe-Humidity Index (BGHI), Equivalent Temperature Index (ETI) and Enthalpy Comfort Index (ECI). The physiological parameters measured were skin surface temperature (TS) and respiratory rate (RR). The comfort indices presented divergent results, the THI and BGHI indices indicated a critical situation, the ETI indicated that the animals would not be under stress, and the ECI indicated that the animals did not exceed the limit value of the comfort zone. The measured wind speed presented results that may have contributed positively to the animal’s comfort. The RF measured in the study presented results superior to the considered range of comfort, ranging from medium-high to high. The TS presented results within the normal range in the morning in the analyzed phases, while in the afternoon this result indicated a situation of thermal stress. The management in bed formed by carnauba straw indicated that the material achieved positive results when considering the TSC aspects, and could be used as an alternative bed material. ICT values were below the values recommended in the literature throughout the experimental period, compromising the composting process. Behaviors were similar throughout the experimental period, with bedtime and feeding behavior being the most frequent, result can be seen as indicative of well-being. The bed made of carnauba straw is an alternative to the compost barn model, allowing thermal comfort to animals. However, the material has low C:N ratio and a fast degradation was observed, for its use a more frequent replacement is necessary.